2020
DOI: 10.1111/nep.13805
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography accurately detects chronic changes in renal histopathology

Abstract: Aim: Renal biopsy is the gold standard for the histological characterization of chronic kidney disease (CKD), of which renal fibrosis is a dominant component, affecting its stiffness. The aim of this study was to investigate the correlation between kidney stiffness obtained by shear wave elastography (SWE) and renal histological fibrosis. Methods: Shear wave elastography assessments were performed in 75 CKD patients who underwent renal biopsy. The SWE-derived estimates of the tissue Young's modulus (YM), given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 31 publications
(76 reference statements)
2
17
0
Order By: Relevance
“…In native kidneys, there are studies using different elastography systems (VTQ, ElastPQ ) that show, as expected, that severe histological changes, both glomerular and tubulointerstitial, are associated with a statistically significant increase in kidney SWS [33,52]. Moreover, in a study performed using the 2D-SWE -SSI elastography method, it has been shown that the degree of glomerulosclerosis and tubulointerstitial fibrosis is associated with higher levels of kidney stiffness and that patients with lower kidney SWS showed a better response to corticotherapy [53].…”
Section: Fibrosis and Elastographysupporting
confidence: 61%
“…In native kidneys, there are studies using different elastography systems (VTQ, ElastPQ ) that show, as expected, that severe histological changes, both glomerular and tubulointerstitial, are associated with a statistically significant increase in kidney SWS [33,52]. Moreover, in a study performed using the 2D-SWE -SSI elastography method, it has been shown that the degree of glomerulosclerosis and tubulointerstitial fibrosis is associated with higher levels of kidney stiffness and that patients with lower kidney SWS showed a better response to corticotherapy [53].…”
Section: Fibrosis and Elastographysupporting
confidence: 61%
“…One of the causes of this could be anisotropy. The architecture of the renal tissue, which is characterized by a high degree of anisotropy, has an impact on the measured kidney SWS, making the results difficult to interpret [41]. In addition to anisotropy, another problem related to renal elastography is the depth of the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…It is is calculated according to the equation: E = 3 cs2, where E = Young's modulus (kPa), cs = shear wave velocity (m/s) [43]. In the study performed by Leong et al on the renal patients who underwent renal biopsy, it was demonstrated that the kidney Young's modulus correlated significantly with intrarenal lesions (p < 0.001) [44].…”
Section: Discussionmentioning
confidence: 99%